HEAVY METALS CONTAMINATIONASSESSMENT FOR SOME IMPORTED AND LOCAL VEGETABLES - Hassoon, H.A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The objective of this study, to was measure concentrations of some heavy metals in various imported and locally produced vegetable crops, including root crops (Turnips ’’Brassica rapa’’ and Carrots ’’Daucus carrota’’), stem crops (Potatoes ’’Solanum tuberosum’’ and Onion ’’Allium sativa’’), leaves (Lettuce ’’Lactuca sativa’’), and fruits (Tomatoes ’’Lycopersicon esculentum’’).These crops were collected from Baghdad central whole sales. X-ray fluorescence spectrometry technique was applied to measure heavy metal concentrations. In the imported vegetables, heavy metal mean concentrations were arranged in the following increasing order: Fe>Zn> Cu>Ni>Co>Cd>Cr>Pb, whereas higher levels of Cr, Fe, Cu, Zn, Cd and Pb (1.2075, 165.995, 37.2275, 43.775, 6.0375, 1.48)mgkg-1, respectively, were found within the locally produced vegetables. High level of Co 3.09625 mgkg-1 was also detected in onion, while, increased concentrations of Ni 7.8675mgkg-1 were found in lettuce collected from local market. Overall significant differences in the heavy metals concentration between imported and locally produced vegetables were observed. The daily intake of four main heavy metals (Cd, Cu, Zn and Pb) had been estimated which revealed highly consumption of Cd (310 and 372 µg per day) for imported and locally vegetables respectively. This study suggests raising the concern of the society and Iraqi government to this problem and to take in consideration its impact on general health and environment.